Zonation Systems and Self-Efficacy: Impact and Influence on Students Science Learning Achievement - Luki Yunita; Evi Sapinatul Bahriah (AL-ISHLAH: Jurnal Pendidikan, 2021)
The purpose of this study is to draw a connection between the zoning system and students' self-efficacy in science learning achievement among senior high school students in Tangerang. The instruments used in this study included self-evaluation sheets, questionnaires, and objective test results from students in science subjects, among other things. Random cluster sampling was used in South Tangerang schools to select the research sample, which consisted of research objects collected from two public high schools. The information gathered was analyzed in a descriptive quantitative manner using the SPSS program, which was developed by IBM. Teachers from chemistry, biology, and physics are involved in this research activity, and they actively participate in research interviews. According to the science teacher's responses, it was discovered that there was an effect on student characteristics associated with zoning-based admission of new students. The science studies teacher was aware of the school's online acceptance of new students pathway, which was implemented by government recommendations. Student confidence in science subjects was rated as high, and a correlation between zoning-based admission of new students and student characteristics was observed.